Pelayanan Sosial Dinas Penataan Ruang Kota Bandung Era Pandemi Covid-19 - Fatya Ayu N'dari; Nanih Machendrawaty; Deden Sumpena (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2022)
Empowerment of top to down role models is an empowerment carried out by the government to the community, carried out through social services in the form of ratifying policies, giving attention, helping community needs in accordance with the duties and functions of the institution, but currently there are problems with public health in the form of the Covid-19 pandemic which disrupting activities, by looking at this problem, social services at the Bandung City Spatial PlanningOffice need to think about efforts for the community. This paper aims to describe the social service program, the service process carried out by the Spatial Planning Office, and the benefits of the program carried out. The method used is qualitative method. Based on the results of the study, the Bandung City Spatial Planning Service carried out social service programs according to their functions, namely planning, utilization, monitoring and control, as well as carrying out funeral services for victims of COVID-19 exposure. The social service process is channeled through E-Government, generating benefits for the community to be involved in spatial planning to meet community needs related to environmental space in the city of Bandung.